Novel Thogotovirus Associated with Febrile Illness and Death, United States, 2014 - Kosoy, Olga I.; Lambert, Amy J.; Hawkinson, Dana J.; Pastula, Daniel M.; Goldsmith, Cynthia S.; Hunt, D. Charles; Staples, J. Erin (Emerging infectious diseases, 2015)
A previously healthy man from eastern Kansas, USA, sought medical care in late spring because of a history of tick bite, fever, and fatigue. The patient had thrombocytopenia and leukopenia and was given doxycycline for a presumed tickborne illness. His condition did not improve. Multiorgan failure developed, and he died 11 days after illness onset from cardiopulmonary arrest. Molecular and serologic testing results for known tickborne pathogens were negative. However, testing of a specimen for antibodies against Heartland virus by using plaque reduction neutralization indicated the presence of another virus. Next-generation sequencing and phylogenetic analysis identified the virus as a novel member of the genus Thogotovirus.